Rare familial 16q21 microdeletions under a linkage peak implicate cadherin 8 (CDH8) in susceptibility to autism and learning disability - Pagnamenta, Alistair T; Khan, Hameed; Walker, Susan; Gerrelli, Dianne; Wing, Kirsty; Bonaglia, Maria Clara; Giorda, Roberto; Berney, Tom; Mani, Elisa; Molteni, Massimo; Pinto, Dalila; Le Couteur, Ann; et al. (Journal of medical genetics, 2011)
BackgroundAutism spectrum disorder (ASD) is characterised by impairments in social communication and by a pattern of repetitive behaviours, with learning disability (LD) typically seen in up to 70% of cases. A recent study using the PPL statistical framework identified a novel region of genetic linkage on chromosome 16q21 that is limited to ASD families with LD.MethodsIn this study, two families with autism and/or LD are described which harbour rare >1.6 Mb microdeletions located within this linkage region. The deletion breakpoints are mapped at base-pair resolution and segregation analysis is performed using a combination of 1M single nucleotide polymorphism (SNP) technology, array comparative genomic hybridisation (CGH), long-range PCR, and Sanger sequencing. The frequency of similar genomic variants in control subjects is determined through analysis of published SNP array data. Expression of CDH8, the only gene disrupted by these microdeletions, is assessed using reverse transcriptase PCR and in situ hybridisation analysis of 9 week human embryos.ResultsThe deletion of chr16: 60 025 584–61 667 839 was transmitted to three of three boys with autism and LD and none of four unaffected siblings, from their unaffected mother. In a second family, an overlapping deletion of chr16: 58 724 527–60 547 472 was transmitted to an individual with severe LD from his father with moderate LD. No copy number variations (CNVs) disrupting CDH8 were observed in 5023 controls. Expression analysis indicates that the two CDH8 isoforms are present in the developing human cortex.ConclusionRare familial 16q21 microdeletions and expression analysis implicate CDH8 in susceptibility to autism and LD.